A study of the effects of adding ice retardant additives to pavement surface course materials - Wright, Michael (2013)
The formation of ice and snow on pavement surfaces is a recurring problem, creating hazardous driving conditions, restricting public mobility as well as having adverse economic effects. Current winter operations primarily consist of the correctly timed application of de-icing chemicals to the pavement surface to prevent hazardous conditions occurring.